Serum Adiponectin, Anemia and Left Ventricular Dimensions in Patients with Cardiac Cachexia - Bozcali, Evin; Polat, Veli; Akbulut, Handan; Yavuzkir, Mustafa Ferzeyn; Karaca, Ilgin (Karger, 2013)
Objectives: Our study aims to determine the role of serum adiponectin in chronic heart failure (CHF) and cardiac cachexia (CC). Methods: Ninety consecutive patients were included in the study. Patients were divided into three groups: 30 CHF patients with CC, 30 CHF patients without CC, and 30 healthy individuals. Adiponectin levels were measured through human ELISA kits. Results: Levels of serum adiponectin were significantly higher in the CHF patients with cachexia in comparison with the other groups (CHF with CC: 58.4 +/- 15.5 ng/ml vs. CHF without CC: 24 +/- 6.7 ng/ml and controls: 7.7 +/- 3.4 ng/ml; p = 0.001). Serum adiponectin was negatively correlated with BMI, high-sensitivity C-reactive protein, and hemoglobin (r = -0.37, p = 0.02; r = -0.29, p = 0.02; r = -0.18, p = 0.03, respectively) in the CHF patients with cachexia. Additionally, serum adiponectin levels were positively correlated with B-type natriuretic protein levels, left ventricle end-diastolic and end-systolic diameters (r = 0.36, p = 0.02; r = 0.46, p = 0.01; r = 0.49, p = 0.006, respectively) in the CHF patients with cachexia. Conclusion: Our findings suggest that adiponectin may play a critical role in the pathogenesis of cardiac remodeling and anemia in CC. Copyright (C) 2013 S. Karger AG, Basel
Keywords: Adiponectin; Heart failure; Anemia; Remodeling